Assessing mental stress on myocardial perfusion and myocardial blood flow in women without obstructive coronary disease: protocol for a mechanistic clinical trial. Issue 12 (8th December 2020) - Ma, Huan; Guo, Lan; Fei, Hongwen; Yin, Han; Wang, Haochen; Bai, Bingqing; Liu, Yuting; Wang, Shuxia; Geng, Qingshan; Jiang, Wei
Abstract : Introduction: Two-thirds of women with symptoms of angina have 'angina with no obstructive coronary artery disease' (ANOCA). Growing evidence supports the use of coronary artery function testing for the diagnosis of ANOCA. Research into the prevalence of mental stress-induced myocardial ischaemia (MSIMI) among women with ANOCA is lacking. MSIMI is common in clinically stable patients with coronary artery disease. It is not associated coronary stenosis but is a prognostic risk factor. Here, we describe the rationale and protocol for a mechanistic clinical trial to test the following hypotheses: (1) that MSIMI is more common in women with ANOCA women than in age-matched and sex-matched controls, and (2) MSIMI is associated with mental stress-induced myocardial blood flow (MBF) change but not with adenosine vasodilator stress-induced MBF change. Methods and analysis: This is a mechanistic clinical trial. 84 women with confirmed ANOCA and 42 aged-matched healthy women (neither angina symptoms nor coronary stenosis) are to be recruited for mental and adenosine vasodilator stress tests. Positron emission tomography CT with ammonia N-13 will be used to evaluate the myocardial perfusion and MBF changes between stress and rest. MSIMI is defined as a summed difference score (SDS) of ≥3 and adenosine stress-induced myocardial ischaemia is defined as an SDS of ≥4. Other assessments include Reactive Hyperemia Index for microvascular endothelial function, peripheral arterial tonometry or digital vasomotor response, and a series of blood and psychometric tests. Ethics and dissemination: This mechanistic clinical trial was approved by the Ethics Committee of Guangdong Provincial People's Hospital. Findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT03982901; Pre-results .